‘Young people think with their eyes’: Proverbs 1:8–19 and cultism in Warri, Delta State - Uroko, Favour C. (Verbum et ecclesia, 2024)
A theological response to the crisis of cult-related activities in Warri is imminent, considering the increasing number of young people joining the group on a daily basis. Proverbs 1:8–19 presents important aphorisms from a wise father to his son, emphasising the importance of avoiding evil company and rejecting the enticement of those who engage in evil behaviour. A literary analysis of the study text reveals three structures: the call to listen (vv. 8–9), peer pressure (vv. 10–16), and consequences for evil-doers and partakers of evil (vv. 17–19). The findings of this study reveal that this thematic analysis forms the basis for young people to join cults and even dropping out of school to practise cultism. The father in the pericope spoke wisely, urging his son not to follow the wrong path and join a bad gang, but to follow the right path that would lead to a happy life, both now and in the future. This study adopted literary criticism. As a recommendation, it is important to conduct mass sensitisation in schools and churches, where young people can be informed about the long and short-term consequences of joining cult groups.Intradisciplinary and/or interdisciplinary implicationsNotwithstanding the father’s counsel, it depends on the son to be wise or foolish. Parents in Warri would be considered wise if they are able to warn their children against cultism and not use their cultists’ children to harass others. Old Testament and Practical Theology were implicated in the study.